NIPBL expression levels in CdLS probands as a predictor of mutation type and phenotypic severity. Issue 2 (29th April 2016) - Kaur, Maninder; Mehta, Devanshi; Noon, Sarah E.; Deardorff, Matthew A.; Zhang, Zhe; Krantz, Ian D.
Abstract : Cornelia de Lange syndrome (CdLS) is a rare, genetically heterogeneous multisystem developmental disorder with a high degree of variability in its clinical presentation. Approximately 65% of probands harbor mutations in genes that encode core components (SMC1A, SMC3, and RAD21) or regulators (NIPBL, HDAC8) of the cohesin complex, of which mutations in NIPBL are the most common. Cohesin plays a canonical role in sister chromatid cohesion during cell division and non‐canonical roles in DNA repair, stem cell maintenance and differentiation, and regulation of gene expression. Disruption of the latter role seems to be the major contributor to the underlying molecular pathogenesis of CdLS. NIPBL is required for loading and unloading the cohesin complex onto chromosomes. The expression levels of NIPBL itself appear to be tightly regulated and highly evolutionarily conserved. Droplet digital PCR was used to quantify NIPBL mRNA expression levels with high precision from a cohort of 37 samples ( NIPBL, SMC1A, SMC3, and HDAC8 mutation positive probands and negative control). Probands with severe forms of CdLS or severe mutation types were found to have lower levels of NIPBL in comparison to phenotypically milder patients and controls. Levels of NIPBL also correlated with the presence of mutations in different CdLS‐causing genes. The data suggests that NIPBL levels are closely correlated with the severity of CdLS and with specific causative genes and types of mutations. ddPCR may provide a tool to assist in diagnostic approaches to CdLS, for genetic counseling and prognosis, and for monitoring potential therapeutic modalities in the future. © 2016 Wiley Periodicals, Inc.